Review and analysis of solar thermal facades. (October 2016) - O'Hegarty, Richard; Kinnane, Oliver; McCormack, Sarah J.
Highlights: Existing solar collectors have been categorised, reviewed and analysed. Areas where there is a paucity of information have been identified including the fixing and framing systems of solar thermal facades as well as cheaper lower efficiency solar thermal façade solutions. A greater range of building integrated solar thermal collectors is required in order for the solar thermal market to expand further. For each application, location and facade typology a specific solution is best suited. Colour inclusion has been identified as one common requirement for building integration by many authors. Using state of the art coating technologies to achieve blue and yellow collectors resulted in efficiency decreases between 3 and 11% when compared to un-coloured collectors. Integrating the collector directly to the walls insulation reduces the heat loss through the back of the collector resulting in efficiency increases for any time and location where the temperature of the collector is greater than the ambient temperature. Overheating risks are primarily associated with flat plate collector based STFs integrated into the building's insulation. Solar thermal façade products based on flat plate collectors or evacuated tube collectors exhibit the highest efficiencies. While, novel and bespoke products often have lower efficiencies they fulfil other functions such as shading and building insulation, which can enhance building efficiency. Novel solar thermal façade solutions include solar collectors integrated into balcony rails, shading devices, louvers, windows or gutters. Abstract: Harnessing solar energy to provide for the thermal needs of buildings is one of the most promising solutions to the global energy issue. Exploiting the additional surface area provided by the building's façade can significantly increase the solar energy output. Developing a range of integrated and adaptable products that do not significantly affect the building's aesthetics is vital to enabling the building integrated solar thermal market to expand and prosper. This work reviews and evaluates solar thermal facades in terms of the standard collector type, which they are based on, and their component make-up. Daily efficiency models are presented, based on a combination of the Hottel Whillier Bliss model and finite element simulation. Novel and market available solar thermal systems are also reviewed and evaluated using standard evaluation methods, based on experimentally determined parameters ISO 9806. Solar thermal collectors integrated directly into the facade benefit from the additional wall insulation at the back; displaying higher efficiencies then an identical collector offset from the facade. Unglazed solar thermal facades with high capacitance absorbers (e.g. concrete) experience a shift in peak maximum energy yield and display a lower sensitivity to ambient conditions than the traditional metallic based unglazed collectors. Glazed solar thermal facades, used for high temperature applications (domestic hot water), result in overheating of the building's interior which can be reduced significantly through the inclusion of high quality wall insulation. For low temperature applications (preheating systems), the cheaper unglazed systems offer the most economic solution. The inclusion of brighter colour for the glazing and darker colour for the absorber shows the lowest efficiency reductions (<4%). Novel solar thermal façade solutions include solar collectors integrated into balcony rails, shading devices, louvers, windows or gutters.